The role of nuclear energy to reduce carbon emission - Yüksel, Serhat; Dinçer, Hasan; Çağlayan, Çağatay; Uluer, Gülsüm Sena (Emerald Group Publishing Ltd., 2023)
Carbon emission is one of the most important problems of today. In this framework, it is important for countries to take the necessary actions to solve this problem. Energy use is one of the most important causes of carbon emissions. Choosing fossil fuels in this process increases the carbon emission problem. Therefore, it is understood that countries should be more sensitive about energy types. In this context, renewable energy (RE) sources are recommended by experts. However, due to some problems of these energy types, it does not seem possible to meet all energy needs from these sources. It is thought that nuclear energy will produce a permanent solution to the carbon emission problem. In this context, it is recommended that the use of nuclear energy be put on the agenda by countries.
Keywords: Carbon Emission; Emission Reduction; Energy; Energy Investments; Environmental Sensitivity; Nuclear Energy